Perancangan Ulang Alat Bantu Proses Assembly Touch Panel Untuk Mengurangi Cacat Produk Menggunakan Metode Quality Function Deployment - anggie eka putri; Irwan, Hery (Jurnal Manajemen Rekayasa dan Inovasi Bisnis, 2024)
The Touch Panel Assembly process is the process of gluing the Touch Panel to the Cover which is used to cover the display on the scale. The gluing process is carried out with the help of a jig with a manual system. The output of the Touch Panel Assembly Process using the current jig is still far from the target and also for the resulting output there are still many Rejects (Peel Off) on one side. This research was conducted to increase output and reduce Peel Off in the touch panel assembly process. The redesign of the jig tool in this study was carried out using the Quality Fungtion Deployment method by basing consumer needs in the design process. Data collection was carried out by distributing questionnaires to 10 people consisting of operators, production leaders and also Quality Control. The results of data collection from the questionnaire found that there is a need to replace the method in the Touch Panel Assembly Process, namely the Pressing method. Therefore, the new jig design can be used by using a lever as a press tool. Then the use of a stopper so that the Touch panel and cover are attached longer without having to be held in the lever area. The output produced after using the new jig design increased by 72% and for Peel off output was reduced by 76% so it is considered that the new jig design can increase production output.